Some Issues in Middle Eastern International Migration (The Pakistan Development Review, 1983)
Recent Middle Eastern migration has created new challenges to both labour-importing and labour-exporting countries. A main concern of the labour importing countries is demo-economic in nature: how to achieve a desired rate of economic growth without creating an adverse balance between expatriate and national populations. The first part of the paper attempts to provide a conceptual frame for such policy analysis illustrated by the case of Kuwait. The second part examines some negative externalities of recent farmers' emigration for Egyptian agricultural productivity.